Faktor-Faktor yang Berhubungan dengan Kejadian Kanker Serviks - Marlina Rajagukguk (Jurnal Ners, 2026)
Cervical cancer is one of the leading causes of morbidity and mortality among women worldwide, with a high disease burden, especially in developing countries including Indonesia. This study aims to analyze the association between age, parity, and family history with the incidence of cervical cancer at Vina Estetika Hospital, Medan, in 2024. This research employed a cross-sectional design with a sample of 260 patients, consisting of 130 cervical cancer patients and 130 non-cancer patients. Data were obtained through medical records and analyzed using Chi-Square tests, correlation, and regression analysis. The results showed that the majority of cervical cancer patients were over 40 years old (89.2%) and there was a significant association between age and the incidence of cervical cancer (p = 0.012). Parity show a significant relationship (p = 0.028), while family history, despite all patients having a negative family history, statistically showed a significant association (p = 0.000). Regression analysis revealed that age, parity, and family history collectively had a highly significant relationship with the incidence of cervical cancer (p = 0.000), contributing 43% to the variation in incidence. This study concludes that age over 40 and parity are the most influential factors associated with cervical cancer, whereas family history is not significantly related. Therefore, preventive efforts such as HPV vaccination, routine screening, and reproductive health education are essential, especially for high-risk women.